The Analysis of Setting and Atmosphere on The Old Man and the Sea: Analisis terhadap latar dan suasana dalam “The Old Man and the Sea” - Tanjung, Muh. Sahrul Ihsan Tanjung; Adistia, Laura; Khusniyah, Nurul Lailatul (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2024)
A good story is not only formed from the plot but can also be formed from the development of setting and atmosphere. This research wants to see how setting and atmosphere can play an active role in shaping and building a story. Especially in the story The Old Man and the Sea. This research is based on the book by E. M. Forster which examines the elements in the novel in his book, namely Aspects of the Novel. This research uses a descriptive qualitative method so that the results of this research are described descriptively and in detail. In the story The Old Man and the Sea, the author uses temporal setting to make the story completely dependent on the setting. So, the novel The Old Man and the Sea is formed from plot development that depends on the setting.